Hierarchical pore configuration in activated coke boosting direct desorption of desulfurization product H2SO4: A combined experimental and computational investigation. (15th August 2021) - Pi, Xinxin; Sun, Fei; Qu, Zhibin; Li, Yang; Gao, Jihui
Graphical abstract: Highlights: Effect of pore configuration on washing regeneration of activated coke is studied. Hierarchical pore is beneficial for both desulfurization and washing regeneration. MD simulations elucidate the pore structure effect on H2 SO4 desorption. The proposed strategy has application potential in industrial SO2 removal process. Abstract: Water washing regeneration has been applied to recover H2 SO4 from desulfurized activated cokes (AC). However, the low regeneration efficiency is the bottleneck which causes inferior cycled desulfurization properties of AC. Herein, we propose that the washing regeneration efficiency can be significantly improved by pore structure regulation of AC. A series of ACs with variable pore configurations were used as model adsorbents to individually investigate the effect of pore structure on the washing-regeneration of desulfurized AC. Cycling desulfurization-regeneration experiments show that the micropore-dominant AC exhibits poor performance of water-washing regeneration. After 10 cycles, the adsorption sulfur capacity of micropore-dominant AC declines to 10.17 mg g −1, only 50% of fresh activated coke. Whereas the hierarchical porous AC containing equivalent volume of micropore and mesopore (0.40 and 0.50 cm 3 g −1 ) has both excellent SO2 removal kinetics and water-washing regeneration performance. Even after 10 cycles, the hierarchical porous AC can still sustain high adsorption sulfur capacity of 70 mg g −1 and excellent water-washing regeneration efficiency of 90%. Molecular dynamic simulations using pore models close to practical AC suggest that the self-diffusion coefficient of H2 SO4 in hierarchical pore is about two times of that in micropore, proving the promoting role of hierarchical porous structure in H2 SO4 desorption. This work not only reveals the relationship of pore configuration with washing regeneration behavior but also provides a facile pore configuration regulation strategy that can substantially improve AC's regeneration efficiency, implying great potentials for applying water-washing regeneration in industrial desulfurization process.